Letter - Chapeltown Trades and Labour Council, 11 May 1926 (page 2)
1926-05-11 "Letter - Chapeltown Trades and Labour Council, 11 May 1926 (page 2)" [g0118002.jpg], 11 May 1926, Chapeltown Trades and Labour Council